2016
DOI: 10.1038/nn.4398
|View full text |Cite
|
Sign up to set email alerts
|

Novel genetic loci underlying human intracranial volume identified through genome-wide association

Abstract: Intracranial volume reflects the maximally attained brain size during development, and remains stable with loss of tissue in late life. It is highly heritable, but the underlying genes remain largely undetermined. In a genome-wide association study of 32,438 adults, we discovered five novel loci for intracranial volume and confirmed two known signals. Four of the loci are also associated with adult human stature, but these remained associated with intracranial volume after adjusting for height. We found a high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
252
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 235 publications
(270 citation statements)
references
References 58 publications
15
252
3
Order By: Relevance
“…In comparison, the 8 ICV SNPs explained 0.099 to 0.27% of the variance [78], the 6 hippocampus SNPs 0.092 to 0.32% [77], the 4 putamen SNPs 0.14 to 0.32, while the 1 SNP associated with caudate explained 0.11% of the trait variance [76]. These results are summarised in Figure Our results align with the hypothesis of a simpler genetic architecture of brain structural phenotypes compared to psychiatric diagnoses.…”
Section: Resultssupporting
confidence: 84%
See 4 more Smart Citations
“…In comparison, the 8 ICV SNPs explained 0.099 to 0.27% of the variance [78], the 6 hippocampus SNPs 0.092 to 0.32% [77], the 4 putamen SNPs 0.14 to 0.32, while the 1 SNP associated with caudate explained 0.11% of the trait variance [76]. These results are summarised in Figure Our results align with the hypothesis of a simpler genetic architecture of brain structural phenotypes compared to psychiatric diagnoses.…”
Section: Resultssupporting
confidence: 84%
“…Another CHARGE paper focused on white matter lesion [565]. In addition to reporting new associated variants, these larger studies also confirmed the previously identified associations [76,78]. In addition, a new manuscript is in preparation that focuses on cortical thickness and surface area.…”
Section: Literature Review Updatesupporting
confidence: 59%
See 3 more Smart Citations